High-toughness ceramic composite electrolyte membrane and large-scale manufacturing method thereof
By introducing nano-scale solid electrolyte powder and aramid fibers into the electrolyte membrane, the problem of insufficient thermal stability, toughness and conductivity of the electrolyte film is solved, and efficient and stable electrolyte membrane preparation and battery performance improvement are achieved.
Patent Information
- Application Number
- CN202411703845.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
AI Technical Summary
The existing electrolyte films have shortcomings in thermal stability, toughness and conductivity, and are difficult to prepare in batches.
Nano-scale solid electrolyte powder is mixed with polymer electrolyte raw materials, added with styrene butadiene rubber emulsion and dispersed in an organic solvent to prepare a ceramicized polymer electrolyte membrane, and aramid fiber reinforced material is introduced on it.
Improve the ionic conductivity, mechanical and thermal stability of the electrolyte membrane, enhance the tensile puncture resistance and flame retardant characteristics, realize stable cycle in a high-voltage and high-current charging and discharge environment, and simplify the large-scale preparation of solid electrolytes .
Smart Images

Figure CN119481259A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a high-toughness ceramic composite electrolyte membrane and a large-scale manufacturing method thereof. Background Art
[0002] The structure of polymer solid electrolytes is highly designable and easy to mass produce. Common polymer solid electrolytes include polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polypropylene oxide (PPO), etc. Among them, PEO polymer solid electrolyte has the characteristics of light weight, flexibility, elasticity, and easy film formation of polymer materials. It is one of the polymer solid electrolytes with the most commercial potential. PEO polymer electrolyte is composed of a polymer matrix and a lithium salt (PEO-LiX system). The ionic conductivity of the system mainly depends on the lithium ion (Li + ) in the PEO chain segment. The oxygen atom in PE0 contains two pairs of lone electrons, which can easily interact with Li + The 2s orbital of Li forms a coordination, which has been confirmed by Fourier transform infrared spectroscopy and Raman spectroscopy. + The conduction in the polymer is carried out through a process of continuous coordination and dissociation with oxygen. + It can migrate within the PE0 chain or between different PEO chains. This migration process mainly occurs in the amorphous region of PE0, which is directly related to the thermal motion and relaxation time of the PE0 chain, and generally conforms to the WLF and VTF equations. Generally speaking, the ionic conductivity of amorphous PEO is higher, 1 to 2 orders of magnitude higher than that of crystalline PE0.
[0003] The commercial application problems faced by PEO electrolytes mainly include the following aspects: (1) The room temperature crystallinity of PEO electrolytes is very high, which limits the local relaxation movement of polymer chain segments and the poor dissociation of lithium salts in the crystalline region. This leads to poor ionic conductivity of PEO electrolytes at room temperature. All-solid-state batteries equipped with PEO electrolytes have poor rate performance at room temperature, but can achieve stable charge and discharge cycles at higher temperatures (60°C); (2) PEO electrolytes have low glass transition temperatures (60°C) and melting points (87°C). They are glassy substances with stable structures at room temperature, but have poor mechanical and thermal stability in high temperature environments. Compared with polyolefin separators, they do not have significant thermal / mechanical safety advantages. At the same time, the limited electrochemical window also makes them unsuitable for high-voltage positive electrode materials with high electrode energy density; (3) Solvated PEO electrolytes are colloidal substances with strong viscoelasticity and poor processability. The dried PEO electrolytes have strong adhesion to glass plates and are difficult to peel off easily. The mass production of PEO electrolytes is not suitable for existing battery material production lines. Summary of the invention
[0004] The purpose of the present invention is to provide a high-toughness ceramic composite electrolyte membrane and a large-scale manufacturing method thereof, so as to solve the technical problems in the prior art that the electrolyte film has poor thermal stability, toughness and conductivity and is difficult to prepare in batches.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a large-scale manufacturing method of a high-toughness ceramic composite electrolyte membrane, comprising the following steps: The nano-scale solid electrolyte powder is mixed with the polymer electrolyte raw material, and then dispersed in an organic solvent after adding styrene-butadiene rubber latex to obtain a ceramic polymer slurry; the ceramic polymer slurry is coated on a copper foil by a coating machine, and dried in a three-section oven to obtain a ceramic polymer electrolyte membrane roll; The ceramic polymer electrolyte membrane roll is rolled into a ceramic polymer electrolyte thin film roll by a double-roll hot press, and then cut into ceramic polymer electrolyte thin films in batches by a slitting machine; The LiTFSI, PEO and EC / DMC are mixed and stirred to obtain an ion gel; the ion gel is mixed with a pre-prepared aramid fiber suspension to obtain an aramid gel; The aramid gel is scraped onto the ceramic polymer electrolyte film, and after drying, it is peeled off from the copper foil to obtain a composite structure aramid fiber reinforced electrolyte membrane, and the composite structure aramid fiber reinforced electrolyte membrane is laminated and pressed to obtain an aramid fiber reinforced composite electrolyte membrane.
[0006] Furthermore, the polymer electrolyte raw material is a mixture of polyethylene oxide, polytetrafluoroethylene and lithium bis(trifluoromethylsulfonyl)imide; the mass ratio of polyethylene oxide and polytetrafluoroethylene in the solid electrolyte powder is (5~20):100:(10~30); the addition ratio of lithium bis(trifluoromethylsulfonyl)imide to polyethylene oxide satisfies EO:Li=(8-20):1; the addition amount of styrene-butadiene rubber latex is 1wt%~2.5wt% of the total mass of the mixture of solid electrolyte powder, polymer electrolyte raw material and styrene-butadiene rubber latex; the organic solvent is acetonitrile solvent; the solid content of the ceramic polymer electrolyte slurry is 40wt%~60wt%; the coating thickness of the coating machine is 80μm~120μm; the drying temperatures of the three-section oven are 90℃, 110℃ and 90℃ respectively.
[0007] Furthermore, the method for preparing the nanoscale solid electrolyte powder comprises the following steps: The solid electrolyte raw material is ball-milled, dried and calcined at high temperature in sequence to obtain a solid electrolyte coarse powder; The solid electrolyte coarse powder is ball-milled, dried and sieved in sequence to obtain high-purity, nano-scale solid electrolyte powder.
[0008] Furthermore, in the step of sequentially ball-milling, drying and high-temperature calcining the solid electrolyte raw material to obtain a solid electrolyte coarse powder, the solid electrolyte raw material is one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide and lithium lanthanum zirconium tantalum oxide; the ball milling medium used in the ball milling process is isopropanol or ethanol, the ball-to-material ratio is (3-5): 1, the rotation speed is 200 rpm-500rpm, and the ball milling time is 4h-6h; the drying temperature is 80°C, and the duration is 8h-12h; the roasting temperature in the high-temperature short calcination process is 850°C-1250°C, the duration is 4-8h, the heating rate is 2-8°C / min, and the cooling rate is 5-15°C / min.
[0009] Furthermore, in the step of sequentially ball-milling, drying and sieving the solid electrolyte coarse powder to obtain a high-purity, nano-scale solid electrolyte powder, the nylon screen of the vibrating screen used in the sieving process has a mesh size of 200 to 500 meshes.
[0010] Furthermore, the pressure of the roller hot press is 2MPa~15Mpa, and the heating temperature is 45°C~80°C; the slitting length of the slitting machine is 50mm~170mm.
[0011] Furthermore, the addition mass ratio of LiTFSI, PEO and EC / DMC is (0.5~1):(1~3):(0.2~0.5); the mass ratio of EC / DMC is (1:1); the mixing mass ratio of the ion gel and the pre-prepared aramid fiber suspension is (1~2):(0.4~0.7); the solid content of the ion gel is 20 wt%~35 wt%; and the solid content of the aramid fiber suspension is 50 wt%~70 wt%.
[0012] Furthermore, the preparation method of the aramid fiber suspension is: dispersing the aramid fiber in a dimethyl sulfoxide liquid containing potassium hydroxide at room temperature, and the dispersing and dissolving time is 1 day to 3 days; the aramid fiber is a para-aramid or meta-aramid long fiber.
[0013] Furthermore, in the step of scraping the aramid gel onto the ceramic polymer electrolyte film, drying it and peeling it off the copper foil to obtain a composite structure aramid fiber reinforced electrolyte membrane, and stacking and pressing multiple layers of the composite structure aramid fiber reinforced electrolyte membrane to obtain an aramid fiber reinforced composite electrolyte membrane, the scraping thickness is 20μm~50μm; the drying temperature is 80℃; the number of stacked layers is 2~5 layers; the pressing process uses a small heated roller press with a pressure of 2μm~10μm, a heating temperature of 60℃~80℃, and a roller gap of 40μm~100μm.
[0014] In a second aspect, the present invention provides a high-toughness ceramic composite electrolyte membrane, which is prepared according to the above-mentioned large-scale manufacturing method of a high-toughness ceramic composite electrolyte membrane.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a high-toughness ceramic composite electrolyte membrane and a large-scale manufacturing method thereof. A zero-dimensional ceramic solid electrolyte powder with good water-oxygen stability is introduced into a PEO polymer electrolyte matrix to break the regularity of the polymer chain, promote the reconstruction of the polymer chain segments and create more amorphous regions. A perchlorate with a high dissociation constant and ionic conductivity is introduced as a lithium salt component. The prepared ceramic polymer electrolyte has a higher ionic conductivity than the traditional PEO polymer electrolyte. The glass transition temperature of the PEO solid electrolyte is low (60°C), and it can maintain good viscoelasticity at room temperature. The mechanical and thermal stability at higher temperatures are poor, and it does not have outstanding thermal and mechanical safety advantages compared to polyolefin separators. In addition, the electrochemical window of the PEO material is limited and is not suitable for high-energy-density high-voltage positive electrode materials. The present invention introduces aramid nanofibers with excellent mechanical properties and thermal stability as fiber reinforcement materials into the ceramic polymer electrolyte to prepare a ceramic polymer electrolyte containing a toughening phase. Compared with traditional PEO electrolytes, ceramic polymer electrolytes containing a toughening phase have stronger tensile puncture resistance and flame retardant properties. At the same time, the highly stable porous aromatic fiber interface layer can resist the erosion of the high-voltage positive electrode and achieve stable cycles under high-voltage and high-current charging and discharging environments. The present invention introduces Teflon materials with strong plasticity to achieve the processability of PEO polymer electrolytes. Teflon, as a common material for dry electrodes, can reduce the viscosity of the mixture when blended with the PEO matrix, making it easy to prepare through a simple scraping process. The ceramic polymer electrolyte proposed in the present invention can rely on existing automatic coating machines and hot-pressing roller machines to achieve large-scale preparation of solid electrolytes, thereby reducing the difficulty of large-scale production of solid electrolytes and R&D investment. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0017] Figure 1 is a preparation flow chart of an embodiment of the present invention; Figure 2 This is a physical picture of the electrolyte membrane according to an embodiment of the present invention. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0019] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0020] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0021] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0022] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0023] The present invention is further described in detail below in conjunction with the accompanying drawings: See also Figure 1 The embodiment of the present invention discloses a high-toughness ceramic composite electrolyte membrane and a large-scale manufacturing method thereof, comprising the following steps: S1, mixing the prepared nano-scale solid electrolyte powder and polymer electrolyte raw material in a certain proportion, adding a small amount of styrene-butadiene rubber latex and fully dispersing them in an organic solvent to prepare a ceramic polymer slurry. Installing the copper foil roll into the winding and unwinding device of the automatic coating machine, adding the prepared ceramic polymer electrolyte slurry into the feeding tank of the automatic coating machine, using the automatic coating machine to continuously coat a ceramic polymer electrolyte membrane with a certain thickness on the copper foil, and after being fully dried in a three-section oven, a ceramic polymer electrolyte membrane roll is prepared.
[0024] It should be noted that in this step, the polymer electrolyte raw materials are polyethylene oxide, polytetrafluoroethylene and lithium bis(trifluoromethylsulfonyl)imide, the mass ratio of solid electrolyte powder, polyethylene oxide and polytetrafluoroethylene is (5-20): 100: (10-30), the mixing ratio of lithium bis(trifluoromethylsulfonyl)imide and polyethylene oxide must satisfy EO / Li = (8-20): 1, the addition amount of styrene-butadiene rubber latex is 1wt%-2.5wt% of the total mass of the mixture, the organic solvent is acetonitrile solvent, and the solid content of the prepared ceramic polymer electrolyte slurry is (40-60) wt%; the copper foil roll used is single-glazed copper foil, the coating thickness of the coating machine is controlled to be (80-120) μm, single-sided coating, the belt speed is 5-15 mm / s, and the drying temperatures of the three-section oven are 90 / 110 / 90°C respectively.
[0025] S2, installing the ceramic polymer electrolyte membrane roll prepared in S1 on a double-roll hot press, and continuously rolling it under a certain pressure and temperature to form a ceramic polymer electrolyte film roll. Installing the film roll into the winding and unwinding device of the slitting machine, and cutting it in batches to obtain ceramic polymer electrolyte films of certain specifications.
[0026] It should be noted that in this step, the pressure of the roller hot press is (2-15) MPa, the heating temperature is (45-80)°C, and the slitting length of the slitting machine is (50-170) mm.
[0027] S3, dispersing the aramid fiber in a dimethyl sulfoxide (DMSO) liquid containing potassium hydroxide (KOH) at room temperature to obtain an aramid fiber suspension. Lithium bis(trifluoromethylsulfonyl)imide (LiTFSi), polyethylene oxide (PEO), ethylene carbonate (EC) / dimethyl carbonate (DMC) (1:1) are mixed in a certain proportion, and then stirred and dispersed into an ion gel. The aramid fiber suspension and the ion gel are fully mixed in a certain proportion to prepare an aramid gel.
[0028] It should be noted that in this step, the aramid fiber is para-aramid or meta-aramid long fiber, the solid content of the aramid fiber suspension is (50-70) wt%, and the dispersion and dissolution time is (1-3) days; the addition ratio of LiTFSI, PEO, and EC / DMC is (0.5-1):(1-3):(0.2-0.5), and the solid content of the prepared ion gel is (20-35) wt%; the mixing ratio of the aramid fiber suspension and the ion gel is (0.4-0.7):(1-2).
[0029] S4, using a scraper to apply the aramid gel prepared in S3 to the ceramic polymer electrolyte film prepared in step 3, and peeling it off from the copper foil after drying to obtain a composite aramid fiber reinforced electrolyte membrane. The electrolyte membrane is stacked together in multiple layers and pressed into an aramid fiber reinforced composite electrolyte membrane of fixed thickness using a small heated roller press, such as Figure 2 a. Figure 2 b and Figure 2 As shown in c.
[0030] It should be noted that in this step, the coating thickness is (20-50) μm, the drying temperature is 80°C, the number of stacked layers is (2-5) layers, the pressure of the small heated roller press is (2-10) MPa, the heating temperature is (60-80)°C, and the roller gap is (40-100) μm.
[0031] In another feasible embodiment of the present invention, the method for preparing the nanoscale solid electrolyte powder in S1 comprises: The raw materials required for preparing the solid electrolyte are mixed and ball-milled, and the ball-milled powder is dried and calcined at high temperature in turn to synthesize the solid electrolyte coarse powder. The obtained solid electrolyte coarse powder is ball-milled, dried and sieved in turn to obtain a high-purity, nano-scale solid electrolyte powder.
[0032] It should be noted that the solid electrolyte is an oxide-type ion conductive ceramic such as lithium titanium aluminum phosphate, lithium germanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, etc. The addition ratio of the raw material powder containing each component element follows the molar ratio of each element in the chemical formula; the equipment used in the ball milling process before and after calcination is a planetary ball mill, the ball milling medium is isopropanol or ethanol, the ball-to-material ratio is (3-5): 1, the rotation speed is 200-500rpm, and the ball milling time is 4-6h; the drying temperature is 80°C, and the duration is 8-12h; the roasting temperature in the high-temperature short calcination synthesis process is 850°C-1250°C, the duration is 4-8h, the heating rate is 2-8°C / min, and the cooling rate is 5-15°C / min; the nylon screen mesh number of the vibrating screen used in the screening process is 200-500 mesh.
[0033] In another feasible embodiment of the present invention, based on the aromatic fiber reinforced composite electrolyte membrane prepared by S4, a lithium metal solid-state battery can be further prepared, which specifically includes the following steps: The aromatic fiber-reinforced composite electrolyte membrane is cut into specifications suitable for the battery size in a glove box, the electrolyte membrane is placed in a lithium-ion electrolyte for swelling, a small amount of electrolyte is stored in the electrolyte body, and then assembled into a button-type or soft-pack lithium metal solid-state battery.
[0034] The composite electrolyte membrane prepared by the present invention has the dual advantages of high ionic conductivity and thermal / mechanical safety, and can be prepared on an industrial scale based on existing equipment. Compared with the PEO electrolyte membrane prepared by the traditional blade coating process, the specific advantages are as follows: (1) The present invention introduces a zero-dimensional ceramic solid electrolyte powder with good water and oxygen stability into a PEO polymer electrolyte matrix to destroy the regularity of the polymer chain, promote the reconstruction of the polymer chain segments and create more amorphous regions, and introduces perchlorate with a higher dissociation constant and ionic conductivity as a lithium salt component. The prepared ceramic polymer electrolyte has higher ionic conductivity than the traditional PEO polymer electrolyte.
[0035] (2) The glass transition temperature of PEO solid electrolyte is low (60°C), and it can maintain good viscoelasticity at room temperature. Its mechanical and thermal stability at higher temperatures are poor, and it does not have outstanding thermal and mechanical safety advantages compared to polyolefin separators. In addition, the electrochemical window of PEO materials is limited and is not suitable for high-energy-density high-voltage positive electrode materials. The present invention introduces aramid nanofibers with excellent mechanical properties and thermal stability as fiber reinforcement materials in ceramic polymer electrolytes to prepare ceramic polymer electrolytes containing toughening phases. Compared with traditional PEO electrolytes, ceramic polymer electrolytes containing toughening phases have strong tensile puncture resistance and flame retardant properties. At the same time, the highly stable porous aromatic fiber interface layer can resist the erosion of the high-voltage positive electrode and achieve stable cycling under high-voltage and high-current charging and discharging environments.
[0036] (3) Having good processability and energy density that meets market demand are the contents that need to be specially considered in the commercial application link. The present invention introduces Teflon material with strong plasticity to achieve the processability of PEO polymer electrolyte. Teflon is a common material for dry electrode. When blended with PEO matrix, it can reduce the viscosity of the mixture, making it easy to prepare by a simple scraping process. The ceramic polymer electrolyte proposed in the present invention can rely on the existing automatic coating machine and hot pressing roller machine to realize the large-scale preparation of solid electrolyte, thereby reducing the difficulty of large-scale production of solid electrolyte and R&D investment.
[0037] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0038] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0039] Embodiment 1: Step 1, take an appropriate amount of lithium aluminum titanium phosphate and put it into a grinding jar and add a number of zirconium oxide balls of different sizes, then put it into a planetary ball mill and add isopropanol as a ball milling medium, the ball-to-material ratio is 3:1, the ball milling speed is set to 200rpm, and the grinding is 4h. After grinding, the powder is dried at 80℃ for 8h, and then the calcination temperature is set to 850℃. A multi-step heating treatment is adopted with a heating rate of 2℃ / min. After reaching 850°C, it is maintained for 4h, and then gradually cooled at a cooling rate of 5℃ / min. After cooling, it is ball milled, dried and sieved with a 200-mesh nylon mesh to obtain a high-purity, nano-scale solid electrolyte powder.
[0040] Step 2, take the LATP solid electrolyte powder with suitable particle size and high purity obtained in step 1, add polyethylene oxide, polytetrafluoroethylene, and lithium bis(trifluoromethylsulfonyl)imide thereto, the mass ratio of LATP solid electrolyte powder, polyethylene oxide and polytetrafluoroethylene is 5:100:10, the mixing ratio of lithium bis(trifluoromethylsulfonyl)imide and polyethylene oxide satisfies EO / Li=8:1, and then add 1wt% styrene-butadiene rubber latex and fully disperse in acetonitrile solvent. The single-light copper foil is installed in the reeling device of the automatic coating machine, and the prepared 40 wt% ceramic polymer electrolyte slurry is added to the feeding tank of the automatic coating machine, the coating thickness of the coating machine is controlled to 80μm Pa, single-sided coating is adopted, the belt speed is set to 5mm / s, and the ceramic polymer electrolyte membrane is continuously coated on the copper foil using an automatic coating machine. The drying temperature of the three-section oven is 90 / 110 / 90°C, and after sufficient drying, a ceramic polymer electrolyte membrane roll is prepared.
[0041] Step 3, install the ceramic polymer electrolyte membrane roll prepared in step 2 on a double roller hot press, set the pressure of the double roller hot press to 2MPa, the heating temperature to 45°C, and continuously roll to form a ceramic polymer electrolyte film roll. Install the film roll into the winding and unwinding device of the slitting machine, set the slitting length of the slitting machine to 50mm, and cut in batches to obtain ceramic polymer electrolyte films.
[0042] Step 4: Disperse the para-aramid fiber in a dimethyl sulfoxide (DMSO) liquid containing potassium hydroxide (KOH) at room temperature to obtain an aramid fiber suspension with a solid content of 50wt%, and disperse and dissolve for 1 day. Lithium bis(trifluoromethylsulfonyl)imide (LiTFSi), polyethylene oxide (PEO), ethylene carbonate (EC) / dimethyl carbonate (DMC) (1:1) are mixed in a ratio of 0.5:1:0.2, and then fully stirred and dispersed to obtain an ion gel with a solid content of 20wt%. Subsequently, the aramid fiber suspension and the ion gel are fully mixed in a ratio of 0.4:1 to prepare an aramid gel.
[0043] Step 5, set the coating thickness to 20μm, use a scraper to apply the aramid gel prepared in step 4 to the ceramic polymer electrolyte film prepared in step 3, set the drying temperature to 80℃, and peel it off from the copper foil after drying to obtain a composite structure of aramid fiber reinforced electrolyte membrane (ANF@CSE). The electrolyte membrane is stacked in 5 layers and pressed into a fixed thickness aramid fiber reinforced composite electrolyte membrane using a small heated roller press with a pressure set to 2 MPa, a heating temperature of 60℃, and a roller gap of 40μm.
[0044] Step 6, cutting the aromatic fiber-reinforced composite electrolyte membrane prepared in step 5 into specifications suitable for the battery size in a glove box, placing the electrolyte membrane in a lithium-ion electrolyte for swelling, accumulating a small amount of electrolyte into the electrolyte body, and then assembling it into a button-type lithium metal solid-state battery.
[0045] Embodiment 2: Step 1, take an appropriate amount of lithium aluminum germanium phosphate and put it into a grinding jar and add a number of zirconium oxide balls of different sizes, then put it into a planetary ball mill and add isopropanol as a ball milling medium, the ball-to-material ratio is 3.25:1, the ball milling speed is set to 238rpm, and the grinding is 4.25h. After grinding, the powder is dried at 80℃ for 8.5h. Then the calcination temperature is set to 900℃, and a multi-step heating treatment is adopted with a heating rate of 2.7℃ / min. After reaching 900℃, it is maintained for 4.5h, and then gradually cooled at a cooling rate of 6.5℃ / min. After cooling, it is ball milled, dried and sieved with a 300-mesh nylon mesh to obtain a high-purity, nano-scale solid electrolyte powder.
[0046] Step 2, taking the LATP solid electrolyte powder with suitable particle size and high purity obtained in step 1, adding polyethylene oxide, polytetrafluoroethylene, and lithium bis(trifluoromethylsulfonyl)imide thereto, the mass ratio of LATP solid electrolyte powder, polyethylene oxide and polytetrafluoroethylene is 6.875:100:12.5, and the mixing ratio of lithium bis(trifluoromethylsulfonyl)imide to polyethylene oxide satisfies EO / Li=9.5:1, and then adding 1.2wt% styrene-butadiene rubber latex and fully dispersing it in acetonitrile solvent. The single-glazed copper foil was installed in the unwinding device of the automatic coating machine, and the prepared 42.5 wt% ceramic polymer electrolyte slurry was added to the feeding tank of the automatic coating machine. The coating thickness of the coating machine was controlled to 85 μm, single-sided coating was adopted, and the tape speed was set to 6.25 mm / s. The ceramic polymer electrolyte membrane was continuously coated on the copper foil using an automatic coating machine. The drying temperatures of the three-section oven were 90 / 110 / 90 °C respectively. After sufficient drying, a ceramic polymer electrolyte membrane roll was prepared.
[0047] Step 3, install the ceramic polymer electrolyte membrane roll prepared in step 2 on a roller hot press, set the pressure of the roller hot press to 3.6MPa, the heating temperature to 49.5°C, and continuously roll to form a ceramic polymer electrolyte film roll. Install the film roll into the winding and unwinding device of the slitting machine, set the slitting length of the slitting machine to 65mm, and cut in batches to obtain ceramic polymer electrolyte films.
[0048] Step 4: Disperse the para-aramid fiber in a dimethyl sulfoxide (DMSO) liquid containing potassium hydroxide (KOH) at room temperature to obtain an aramid fiber suspension with a solid content of 52.5wt%, and disperse and dissolve for 2 days. Lithium bis(trifluoromethylsulfonyl)imide (LiTFSi), polyethylene oxide (PEO), ethylene carbonate (EC) / dimethyl carbonate (DMC) (1:1) are mixed in a ratio of 0.5625:1.25:0.2375, and then fully stirred and dispersed to obtain an ion gel with a solid content of 21.875wt%. Subsequently, the aramid fiber suspension and the ion gel are fully mixed in a ratio of 0.4375:1.125 to prepare an aramid gel.
[0049] Step 5, set the coating thickness to 24μm, use a scraper to apply the aramid gel prepared in step 4 to the ceramic polymer electrolyte film prepared in step 3, set the drying temperature to 80℃, and peel it off from the copper foil after drying to obtain a composite structure of aramid fiber reinforced electrolyte membrane (ANF@CSE). The electrolyte membrane is stacked in 3 layers and a small heated roller press is used with a pressure set to 3MPa, a heating temperature of 62.5℃, and a roller gap of 48μm to press it into a fixed thickness aramid fiber reinforced composite electrolyte membrane.
[0050] Step 6, cutting the aromatic fiber-reinforced composite electrolyte membrane prepared in step 5 into specifications suitable for the battery size in a glove box, placing the electrolyte membrane in a lithium-ion electrolyte for swelling, accumulating a small amount of electrolyte into the electrolyte body, and then assembling it into a button-type lithium metal solid-state battery.
[0051] Embodiment 3: Step 1, take an appropriate amount of lithium lanthanum zirconium oxide and put it into a grinding jar and add several zirconium oxide balls of different sizes, then put it into a planetary ball mill and add isopropanol as a ball milling medium, the ball-to-material ratio is 3.5:1, the ball milling speed is set to 275rpm, and the grinding is 4.5h. After grinding, the powder is dried at 80℃ for 9h, and then the calcination temperature is set to 950℃. Multi-step heating treatment is adopted with a heating rate of 3.5℃ / min. After reaching 950℃, it is maintained for 5h, and then gradually cooled at a cooling rate of 7.5℃ / min. After cooling, it is ball milled, dried and sieved with a 400-mesh nylon mesh to obtain a high-purity, nano-scale solid electrolyte powder.
[0052] Step 2, taking the LATP solid electrolyte powder with suitable particle size and high purity obtained in step 1, adding polyethylene oxide, polytetrafluoroethylene, and lithium bis(trifluoromethylsulfonyl)imide thereto, the mass ratio of LATP solid electrolyte powder, polyethylene oxide and polytetrafluoroethylene is 8.75:100:15, and the mixing ratio of lithium bis(trifluoromethylsulfonyl)imide to polyethylene oxide satisfies EO / Li=11:1, and then adding 1.375wt% styrene-butadiene rubber latex and fully dispersing it in acetonitrile solvent. The single-glazed copper foil was installed in the unwinding device of the automatic coating machine, and the prepared 45wt% ceramic polymer electrolyte slurry was added to the feeding tank of the automatic coating machine. The coating thickness of the coating machine was controlled to 90μm, single-sided coating was adopted, the tape speed was set to 7.5mm / s, and the ceramic polymer electrolyte membrane was continuously coated on the copper foil by the automatic coating machine. The drying temperatures of the three-section oven were 90 / 110 / 90℃ respectively. After sufficient drying, a ceramic polymer electrolyte membrane roll was prepared.
[0053] Step 3, install the ceramic polymer electrolyte membrane roll prepared in step 2 on a roller hot press, set the pressure of the roller hot press to 5.25MPa, the heating temperature to 53.75°C, and continuously roll to form a ceramic polymer electrolyte film roll. Install the film roll into the winding and unwinding device of the slitting machine, set the slitting length of the slitting machine to 80mm, and cut in batches to obtain ceramic polymer electrolyte films.
[0054] Step 4: Disperse the meta-aramid fiber in a dimethyl sulfoxide (DMSO) liquid containing potassium hydroxide (KOH) at room temperature to obtain an aramid fiber suspension with a solid content of 55wt%, and disperse and dissolve for 3 days. Lithium bis(trifluoromethylsulfonyl)imide (LiTFSi), polyethylene oxide (PEO), ethylene carbonate (EC) / dimethyl carbonate (DMC) (1:1) are mixed in a ratio of 0.625:1.5:0.275, and then fully stirred and dispersed to obtain an ion gel with a solid content of 23.75wt%. Subsequently, the aramid fiber suspension and the ion gel are fully mixed in a ratio of 0.475:1.25 to prepare an aramid gel.
[0055] Step 5, set the coating thickness to 28μm, use a scraper to apply the aramid gel prepared in step 4 to the ceramic polymer electrolyte film prepared in step 3, set the drying temperature to 80°C, and peel it off from the copper foil after drying to obtain a composite structure of aramid fiber reinforced electrolyte membrane (ANF@CSE). The electrolyte membrane is stacked in 3 layers and a small heated roller press is used with a pressure set to 4MPa, a heating temperature of 65°C, and a roller gap of 55μm to press it into a fixed thickness aramid fiber reinforced composite electrolyte membrane.
[0056] Step 6, cutting the aromatic fiber-reinforced composite electrolyte membrane prepared in step 5 into specifications suitable for the battery size in a glove box, placing the electrolyte membrane in a lithium-ion electrolyte for swelling, accumulating a small amount of electrolyte into the electrolyte body, and then assembling it into a button-type lithium metal solid-state battery.
[0057] Embodiment 4: Step 1, take an appropriate amount of lithium lanthanum zirconium tantalum oxide and put it into a grinding jar and add a number of zirconium oxide balls of different sizes, then put it into a planetary ball mill and add ethanol as a ball milling medium, the ball-to-material ratio is 3.75:1, the ball milling speed is set to 313rpm, and the grinding is 4.75h. After grinding, the powder is dried at 80℃ for 9.5h. Then the calcination temperature is set to 1000℃, and a multi-step heating treatment is adopted with a heating rate of 4.25℃ / min. After reaching 1000°C, it is maintained for 5.5h, and then a gradual cooling treatment is carried out with a cooling rate of 8.75℃ / min. After cooling, it is ball milled, dried and sieved with a 500-mesh nylon mesh to obtain a high-purity, nano-scale solid electrolyte powder.
[0058] Step 2, take the LATP solid electrolyte powder with suitable particle size and high purity obtained in step 1, add polyethylene oxide, polytetrafluoroethylene, bis(trifluoromethylsulfonyl)imide lithium therein, the mass ratio of LATP solid electrolyte powder, polyethylene oxide and polytetrafluoroethylene is 10.625:100:17.5, the mixing ratio of bis(trifluoromethylsulfonyl)imide lithium and polyethylene oxide satisfies EO / Li=12.5:1, and then 1.5625wt% styrene-butadiene rubber latex is added and fully dispersed in acetonitrile solvent. Single light copper foil is installed in the reeling device of automatic coating machine, and the prepared 47.5wt% ceramic polymer electrolyte slurry is added to the feeding tank of automatic coating machine, the coating thickness of coating machine is controlled to be 95μm, single-sided coating is adopted, and the belt speed is set to 8.75mm / s, and ceramic polymer electrolyte membrane is continuously coated on copper foil using automatic coating machine, and the drying temperature of three-section oven is set to 90°C, which is fully dried.
[0059] Step 3, install the ceramic polymer electrolyte membrane roll prepared in step 2 on a roller hot press, set the pressure of the roller hot press to 6.8MPa, the heating temperature to 58.5°C, and continuously roll to form a ceramic polymer electrolyte film roll. Install the film roll into the winding and unwinding device of the slitting machine, set the slitting length of the slitting machine to 95mm, and cut in batches to obtain ceramic polymer electrolyte films.
[0060] Step 4: Disperse the meta-aramid fiber in a dimethyl sulfoxide (DMSO) liquid containing potassium hydroxide (KOH) at room temperature to obtain an aramid fiber suspension with a solid content of 57.5wt%, and disperse and dissolve for 1 day. Lithium bis(trifluoromethylsulfonyl)imide (LiTFSi), polyethylene oxide (PEO), ethylene carbonate (EC) / dimethyl carbonate (DMC) (1:1) are mixed in a ratio of 0.6875:1.75:0.3125, and then fully stirred and dispersed to obtain an ion gel with a solid content of 25.625wt%. Subsequently, the aramid fiber suspension and the ion gel are fully mixed in a ratio of 0.5125: 1.375 to prepare an aramid gel.
[0061] Step 5, set the coating thickness to 31μm, use a scraper to apply the aramid gel prepared in step 4 to the ceramic polymer electrolyte film prepared in step 3, set the drying temperature to 80℃, and peel it off from the copper foil after drying to obtain a composite structure of aramid fiber reinforced electrolyte membrane (ANF@CSE). The electrolyte membrane is stacked in 4 layers and pressed into a fixed thickness aramid fiber reinforced composite electrolyte membrane using a small heated roller press with a pressure set to 5MPa, a heating temperature of 67.5℃, and a roller gap of 63μm.
[0062] Step 6, cutting the aromatic fiber-reinforced composite electrolyte membrane prepared in step 5 into specifications suitable for the battery size in a glove box, placing the electrolyte membrane in a lithium-ion electrolyte for swelling, accumulating a small amount of electrolyte into the electrolyte body, and then assembling it into a soft-pack lithium metal solid-state battery.
[0063] Embodiment 5: Step 1, take an appropriate amount of lithium lanthanum zirconium tantalum oxide and put it into a grinding jar and add a number of zirconium oxide balls of different sizes, then put it into a planetary ball mill and add ethanol as a ball milling medium, the ball-to-material ratio is 4:1, the ball milling speed is set to 350rpm, and the grinding is for 5 hours. After grinding, the powder is dried at 80°C for 10 hours, and then the roasting temperature is set to 1050°C. A multi-step heating treatment is adopted with a heating rate of 5°C / min. After reaching 1050°C, it is maintained for 6 hours, and then a gradual cooling treatment is carried out with a cooling rate of 10°C / min. After cooling, it is ball milled, dried and sieved with a 350-mesh nylon mesh to obtain a high-purity, nano-scale solid electrolyte powder.
[0064] Step 2, taking the LATP solid electrolyte powder with suitable particle size and high purity obtained in step 1, adding polyethylene oxide, polytetrafluoroethylene, and lithium bis(trifluoromethylsulfonyl)imide thereto, the mass ratio of LATP solid electrolyte powder, polyethylene oxide and polytetrafluoroethylene is 12.5:100:20, and the mixing ratio of lithium bis(trifluoromethylsulfonyl)imide to polyethylene oxide satisfies EO / Li=14:1, and then adding 1.75wt% styrene-butadiene rubber latex and fully dispersing it in acetonitrile solvent. The single-glazed copper foil was installed in the unwinding device of the automatic coating machine, and the prepared 50wt% ceramic polymer electrolyte slurry was added to the feeding tank of the automatic coating machine. The coating thickness of the coating machine was controlled to be 100μm, single-sided coating was adopted, the tape speed was set to 10mm / s, and the ceramic polymer electrolyte membrane was continuously coated on the copper foil by the automatic coating machine. The drying temperatures of the three-section oven were 90 / 110 / 90℃ respectively. After sufficient drying, a ceramic polymer electrolyte membrane roll was prepared.
[0065] Step 3, install the ceramic polymer electrolyte membrane roll prepared in step 2 on a roller hot press, set the pressure of the roller hot press to 8.5MPa, the heating temperature to 62.5°C, and continuously roll to form a ceramic polymer electrolyte film roll. Install the film roll into the winding and unwinding device of the slitting machine, set the slitting length of the slitting machine to 110mm, and cut in batches to obtain ceramic polymer electrolyte films.
[0066] Step 4: Disperse the meta-aramid fiber in a dimethyl sulfoxide (DMSO) liquid containing potassium hydroxide (KOH) at room temperature to obtain an aramid fiber suspension with a solid content of 60wt%, and disperse and dissolve for 2 days. Lithium bis(trifluoromethylsulfonyl)imide (LiTFSi), polyethylene oxide (PEO), ethylene carbonate (EC) / dimethyl carbonate (DMC) (1:1) are mixed in a ratio of 0.75:2:0.35, and then fully stirred and dispersed to obtain an ion gel with a solid content of 27.5wt%. Subsequently, the aramid fiber suspension and the ion gel are fully mixed in a ratio of 0.55:1.5 to prepare an aramid gel.
[0067] Step 5, set the coating thickness to 35 μm, use a scraper to apply the aramid gel prepared in step 4 to the ceramic polymer electrolyte film prepared in step 3, set the drying temperature to 80 ° C, and peel it off from the copper foil after drying to obtain a composite structure of aramid fiber reinforced electrolyte membrane. The electrolyte membrane is stacked in two layers and a small heated roller press is used, the pressure is set to 6 MPa, the heating temperature is 70 ° C, and the roller gap is 70 μm, and pressed into a fixed thickness of aramid fiber reinforced composite electrolyte membrane.
[0068] Step 6, cutting the aromatic fiber-reinforced composite electrolyte membrane prepared in step 5 into specifications suitable for the battery size in a glove box, placing the electrolyte membrane in a lithium-ion electrolyte for swelling, accumulating a small amount of electrolyte into the electrolyte body, and then assembling it into a button-structured lithium metal solid-state battery.
[0069] Embodiment 6: Step 1, take an appropriate amount of lithium aluminum germanium phosphate and put it into a grinding jar and add a number of zirconium oxide balls of different sizes, then put it into a planetary ball mill and add isopropanol as a ball milling medium, the ball-to-material ratio is 4.25:1, the ball milling speed is set to 388rpm, and the grinding is 5.25h. After grinding, the powder is dried at 80℃ for 10.5h. Then the calcination temperature is set to 1100℃, and a multi-step heating treatment is adopted with a heating rate of 5.75℃ / min. After reaching 1100°C, it is maintained for 6.5h, and then gradually cooled at a cooling rate of 11.25℃ / min. After cooling, it is ball milled, dried and sieved with a 400-mesh nylon mesh to obtain a high-purity, nano-scale solid electrolyte powder.
[0070] Step 2, taking the LATP solid electrolyte powder with suitable particle size and high purity obtained in step 1, adding polyethylene oxide, polytetrafluoroethylene, and lithium bis(trifluoromethylsulfonyl)imide thereto, the mass ratio of LATP solid electrolyte powder, polyethylene oxide and polytetrafluoroethylene is 14.375:100:22.5, and the mixing ratio of lithium bis(trifluoromethylsulfonyl)imide to polyethylene oxide satisfies EO / Li=15.5:1, and then adding 1.975wt% styrene-butadiene rubber latex and fully dispersing it in acetonitrile solvent. The single-glazed copper foil was installed in the unwinding device of the automatic coating machine, and the prepared 52.5wt% ceramic polymer electrolyte slurry was added to the feeding tank of the automatic coating machine. The coating thickness of the coating machine was controlled to 105μm. Single-sided coating was adopted, and the tape speed was set to 11.25mm / s. The ceramic polymer electrolyte membrane was continuously coated on the copper foil by the automatic coating machine. The drying temperatures of the three-section oven were 90 / 110 / 90℃ respectively. After sufficient drying, a ceramic polymer electrolyte membrane roll was prepared.
[0071] Step 3, install the ceramic polymer electrolyte membrane roll prepared in step 2 on a roller hot press, set the pressure of the roller hot press to 10.125MPa, the heating temperature to 66.85°C, and continuously roll to form a ceramic polymer electrolyte film roll. Install the film roll into the winding and unwinding device of the slitting machine, set the slitting length of the slitting machine to 125μm, and cut in batches.
[0072] Step 4: Disperse the para-aramid fiber in a dimethyl sulfoxide (DMSO) liquid containing potassium hydroxide (KOH) at room temperature to obtain an aramid fiber suspension with a solid content of 62.5wt%, and disperse and dissolve for 3 days. Lithium bis(trifluoromethylsulfonyl)imide (LiTFSi), polyethylene oxide (PEO), ethylene carbonate (EC) / dimethyl carbonate (DMC) (1:1) are mixed in a ratio of 0.8125:2.25:0.3875, and then fully stirred and dispersed to obtain an ion gel with a solid content of 29.375wt%. Subsequently, the aramid fiber suspension and the ion gel are fully mixed in a ratio of 0.5875:1.625 to prepare an aramid gel.
[0073] Step 5, set the coating thickness to 39mm, use a scraper to apply the aramid gel prepared in step 4 to the ceramic polymer electrolyte film prepared in step 3, set the drying temperature to 80°C, and peel it off from the copper foil after drying to obtain a composite aramid fiber reinforced electrolyte membrane. The electrolyte membrane is stacked in 3 layers and a small heated roller press is used, the pressure is set to 7MPa, the heating temperature is 72.5°C, and the roller gap is 78μm, and pressed into a fixed thickness aramid fiber reinforced composite electrolyte membrane.
[0074] Step 6, cutting the aromatic fiber-reinforced composite electrolyte membrane prepared in step 5 into specifications suitable for the battery size in a glove box, placing the electrolyte membrane in a lithium-ion electrolyte for swelling, accumulating a small amount of electrolyte into the electrolyte body, and then assembling it into a button-type lithium metal solid-state battery.
[0075] Embodiment 7: Step 1, take an appropriate amount of lithium aluminum titanium phosphate and put it into a grinding jar and add a number of zirconium oxide balls of different sizes, then put it into a planetary ball mill and add ethanol as a ball milling medium, the ball-to-material ratio is 4.5:1, the ball milling speed is set to 425rpm, and the grinding is 5.5h. After grinding, the powder is dried at 80℃ for 11h, and then the calcination temperature is set to 1150℃, and a multi-step heating treatment is adopted with a heating rate of 6.5℃ / min. After reaching 1150°C, it is maintained for 7h, and then gradually cooled at a cooling rate of 12.5℃ / min. After cooling, it is ball milled, dried and sieved with a 400-mesh nylon mesh to obtain a high-purity, nano-scale solid electrolyte powder.
[0076] Step 2, taking the LATP solid electrolyte powder with suitable particle size and high purity obtained in step 1, adding polyethylene oxide, polytetrafluoroethylene, and lithium bis(trifluoromethylsulfonyl)imide thereto, the mass ratio of LATP solid electrolyte powder, polyethylene oxide and polytetrafluoroethylene is 16.25:100:25, and the mixing ratio of lithium bis(trifluoromethylsulfonyl)imide to polyethylene oxide satisfies EO / Li=17:1, and then adding 2.125wt% styrene-butadiene rubber latex and fully dispersing it in acetonitrile solvent. The single-glazed copper foil was installed in the unwinding device of the automatic coating machine, and the prepared 55wt% ceramic polymer electrolyte slurry was added to the feeding tank of the automatic coating machine. The coating thickness of the coating machine was controlled to be 110μm, single-sided coating was adopted, the tape speed was set to 12.5mm / s, and the ceramic polymer electrolyte membrane was continuously coated on the copper foil by the automatic coating machine. The drying temperatures of the three-section oven were 90 / 110 / 90℃ respectively. After sufficient drying, a ceramic polymer electrolyte membrane roll was prepared.
[0077] Step 3, install the ceramic polymer electrolyte membrane roll prepared in step 2 on a roller hot press, set the pressure of the roller hot press to 11.75MPa, the heating temperature to 71.25°C, and continuously roll to form a ceramic polymer electrolyte film roll. Install the film roll into the winding and unwinding device of the slitting machine, set the slitting length of the slitting machine to 140μm, and cut in batches.
[0078] Step 4: Disperse the para-aramid fiber in a dimethyl sulfoxide (DMSO) liquid containing potassium hydroxide (KOH) at room temperature to obtain an aramid fiber suspension with a solid content of 65wt%, and disperse and dissolve for 1 day. Lithium bis(trifluoromethylsulfonyl)imide (LiTFSi), polyethylene oxide (PEO), ethylene carbonate (EC) / dimethyl carbonate (DMC) (1:1) are mixed in a ratio of 0.875:2.5:0.425, and then fully stirred and dispersed to obtain an ion gel with a solid content of 31.25wt%. Subsequently, the aramid fiber suspension and the ion gel are fully mixed in a ratio of 0.625:1.75 to prepare an aramid gel.
[0079] Step 5, set the coating thickness to 43μm, use a scraper to apply the aramid gel prepared in step 4 to the ceramic polymer electrolyte film prepared in step 3, set the drying temperature to 80℃, and peel it off from the copper foil after drying to obtain a composite structure of aramid fiber reinforced electrolyte membrane (ANF@CSE). The electrolyte membrane is stacked in 4 layers and pressed into a fixed thickness aramid fiber reinforced composite electrolyte membrane using a small heated roller press with a pressure set to 8MPa, a heating temperature of 75℃, and a roller gap of 85μm.
[0080] Step 6, cutting the aromatic fiber-reinforced composite electrolyte membrane prepared in step 5 into specifications suitable for the battery size in a glove box, placing the electrolyte membrane in a lithium-ion electrolyte for swelling, accumulating a small amount of electrolyte into the electrolyte body, and then assembling it into a soft-pack lithium metal solid-state battery.
[0081] Embodiment 8: Step 1, take an appropriate amount of lithium lanthanum zirconium oxide and put it into a grinding jar and add a number of zirconium oxide balls of different sizes, then put it into a planetary ball mill and add ethanol as a ball milling medium, the ball-to-material ratio is 4.75:1, the ball milling speed is set to 463rpm, and the grinding is 5.75h. After grinding, the powder is dried at 80℃ for 11.5h. Then the calcination temperature is set to 1200℃, and a multi-step heating treatment is adopted with a heating rate of 7.25℃ / min. After reaching 1200°C, it is maintained for 7.5h, and then gradually cooled at a cooling rate of 13.75℃ / min. After cooling, it is ball milled, dried and sieved with a 500-mesh nylon mesh to obtain a high-purity, nano-scale solid electrolyte powder.
[0082] Step 2, taking the LATP solid electrolyte powder with suitable particle size and high purity obtained in step 1, adding polyethylene oxide, polytetrafluoroethylene, and lithium bis(trifluoromethylsulfonyl)imide thereto, the mass ratio of LATP solid electrolyte powder, polyethylene oxide and polytetrafluoroethylene is 18.125:100:27.5, and the mixing ratio of lithium bis(trifluoromethylsulfonyl)imide to polyethylene oxide satisfies EO / Li=18.5:1, and then adding 2.325wt% styrene-butadiene rubber latex and fully dispersing it in acetonitrile solvent. The single-glazed copper foil was installed in the unwinding and rewinding device of the automatic coating machine, and the prepared 57.5wt% ceramic polymer electrolyte slurry was added to the feeding tank of the automatic coating machine. The coating thickness of the coating machine was controlled to be 115μm. Single-sided coating was adopted, and the tape speed was set to 13.75mm / s. The ceramic polymer electrolyte membrane was continuously coated on the copper foil by the automatic coating machine. The drying temperatures of the three-section oven were 90 / 110 / 90℃ respectively. After sufficient drying, a ceramic polymer electrolyte membrane roll was prepared.
[0083] Step 3, install the ceramic polymer electrolyte membrane roll prepared in step 2 on a roller hot press, set the pressure of the roller hot press to 13.75MPa, the heating temperature to 75.25°C, and continuously roll to form a ceramic polymer electrolyte film roll. Install the film roll into the reeling and unwinding device of the slitting machine, set the slitting length of the slitting machine to 155mm, and cut in batches.
[0084] Step 4: Disperse the meta-aramid fiber in a dimethyl sulfoxide (DMSO) liquid containing potassium hydroxide (KOH) at room temperature to obtain an aramid fiber suspension with a solid content of 67.5wt%, and disperse and dissolve for 2 days. Lithium bis(trifluoromethylsulfonyl)imide (LiTFSi), polyethylene oxide (PEO), ethylene carbonate (EC) / dimethyl carbonate (DMC) (1:1) are mixed in a ratio of 0.9375:2.75:0.4625, and then fully stirred and dispersed to obtain an ion gel with a solid content of 33.125wt%. Subsequently, the aramid fiber suspension and the ion gel are fully mixed in a ratio of 0.6625:1.875 to prepare an aramid gel.
[0085] Step 5, set the coating thickness to 46μm, use a scraper to apply the aramid gel prepared in step 4 to the ceramic polymer electrolyte film prepared in step 3, set the drying temperature to 80℃, and peel it off from the copper foil after drying to obtain a composite structure of aramid fiber reinforced electrolyte membrane (ANF@CSE). The electrolyte membrane is stacked in 3 layers and a small heated roller press is used with a pressure set to 9MPa, a heating temperature of 77.5℃, and a roller gap of 92μm to press it into a fixed thickness aramid fiber reinforced composite electrolyte membrane.
[0086] Step 6, cutting the aromatic fiber-reinforced composite electrolyte membrane prepared in step 5 into specifications suitable for the battery size in a glove box, placing the electrolyte membrane in a lithium-ion electrolyte for swelling, accumulating a small amount of electrolyte into the electrolyte body, and then assembling it into a button-structured lithium metal solid-state battery.
[0087] Embodiment 9: Step 1, take an appropriate amount of lithium lanthanum zirconium oxide and put it into a grinding jar and add a number of zirconium oxide balls of different sizes, then put it into a planetary ball mill and add ethanol as a ball milling medium, the ball-to-material ratio is 5:1, the ball milling speed is set to 500rpm, and the grinding is for 6 hours. After grinding, the powder is dried at 80°C for 12 hours, and then the calcination temperature is set to 1250°C. A multi-step heating treatment is adopted with a heating rate of 8°C / min. After reaching 1250°C, it is maintained for 8 hours, and then a gradual cooling treatment is carried out with a cooling rate of 15°C / min. After cooling, it is ball milled, dried and sieved with a 500-mesh nylon mesh to obtain a high-purity, nano-scale solid electrolyte powder.
[0088] Step 2, take the LATP solid electrolyte powder with suitable particle size and high purity obtained in step 1, add polyethylene oxide, polytetrafluoroethylene, and lithium bis(trifluoromethylsulfonyl imide), the mass ratio of LATP solid electrolyte powder, polyethylene oxide and polytetrafluoroethylene is 20:100:30, the mixing ratio of lithium bis(trifluoromethylsulfonyl imide and polyethylene oxide satisfies EO / Li=20:1, and then add 2.5wt% styrene-butadiene rubber latex and fully disperse in acetonitrile solvent. The single-light copper foil is installed in the reeling device of the automatic coating machine, and the prepared 60wt% ceramic polymer electrolyte slurry is added to the feeding tank of the automatic coating machine, the coating thickness of the coating machine is controlled to be 120μm, single-sided coating is adopted, the belt speed is set to 15mm / s, and the ceramic polymer electrolyte membrane is continuously coated on the copper foil using an automatic coating machine, and the drying temperature of the three-section oven is 90 / 110 / 90°C, and after sufficient drying, a ceramic polymer electrolyte membrane roll is prepared.
[0089] Step 3, install the ceramic polymer electrolyte membrane roll prepared in step 2 on a roller hot press, set the pressure of the roller hot press to 15MPa, the heating temperature to 80°C, and continuously roll to form a ceramic polymer electrolyte film roll. Install the film roll into the winding and unwinding device of the slitting machine, set the slitting length of the slitting machine to 170mm, and cut in batches.
[0090] Step 4: Disperse the meta-aramid fiber in a dimethyl sulfoxide (DMSO) liquid containing potassium hydroxide (KOH) at room temperature to obtain an aramid fiber suspension with a solid content of 70wt%, and disperse and dissolve for 3 days. Lithium bis(trifluoromethylsulfonyl)imide (LiTFSi), polyethylene oxide (PEO), ethylene carbonate (EC) / dimethyl carbonate (DMC) (1:1) are mixed in a ratio of 1:3:0.5, and then fully stirred and dispersed to obtain an ion gel with a solid content of 35wt%, and then the aramid fiber suspension and the ion gel are fully mixed in a ratio of 0.7:2 to prepare an aramid gel.
[0091] Step 5, set the coating thickness to 50 μm, use a scraper to apply the aramid gel prepared in step 4 to the ceramic polymer electrolyte film prepared in step 3, set the drying temperature to 80 ° C, and peel it off from the copper foil after drying to obtain a composite structure of aramid fiber reinforced electrolyte membrane. The electrolyte membrane is stacked in 5 layers and a small heated roller press is used, the pressure is set to 10 MPa, the heating temperature is 80 ° C, and the roller gap is 100 μm, and pressed into a fixed thickness of aramid fiber reinforced composite electrolyte membrane.
[0092] Step 6, cutting the aromatic fiber-reinforced composite electrolyte membrane prepared in step 5 into specifications suitable for the battery size in a glove box, placing the electrolyte membrane in a lithium-ion electrolyte for swelling, accumulating a small amount of electrolyte into the electrolyte body, and then assembling it into a button-structured lithium metal solid-state battery.
[0093] Embodiment 10: The difference from Example 8 is that the solid electrolyte raw material is lithium aluminum titanium phosphate, and the calcination temperature set for high-temperature calcination is 950°C.
[0094] Embodiment 11: The difference from Example 10 is that the mass ratio of the solid electrolyte powder, polyethylene oxide and polytetrafluoroethylene is 13:100:15.
[0095] Embodiment 12: The difference from Example 11 is that the coating thickness of the coater is controlled to be 120 μm Pa, the belt speed is 6 mm / s, and the drying temperature of the three-section oven is 90° C.
[0096] Embodiment 13: The difference from Example 12 is that in step 3, the pressure of the roller hot press is 6 MPa, the heating temperature is 50°C, and the slitting length of the slitting machine is 60 mm.
[0097] Embodiment 14: The difference from Example 13 is that the aramid fiber in step 4 is para-aramid.
[0098] Embodiment 15: The difference from Example 14 is that in step 4, the addition ratio of LiTFSI, PEO, and EC / DMC is 0.7:1.5:0.3.
[0099] Embodiment 16: The difference from Example 15 is that the coating thickness in step 5 is 30 μm and the number of superimposed layers is 5. The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A large-scale manufacturing method for a high-toughness ceramic composite electrolyte membrane, characterized in that: The following steps are involved: The nano-scale solid electrolyte powder is mixed with the polymer electrolyte raw material, and then dispersed in an organic solvent after adding styrene-butadiene rubber latex to obtain a ceramic polymer slurry; the ceramic polymer slurry is coated on a copper foil by a coating machine, and dried in a three-section oven to obtain a ceramic polymer electrolyte membrane roll; The ceramic polymer electrolyte membrane roll is rolled into a ceramic polymer electrolyte thin film roll by a double-roll hot press, and then cut into ceramic polymer electrolyte thin films in batches by a slitting machine; The LiTFSI, PEO and EC / DMC are mixed and stirred to obtain an ion gel; the ion gel is mixed with a pre-prepared aramid fiber suspension to obtain an aramid gel; The aramid gel is scraped onto the ceramic polymer electrolyte film, and after drying, it is peeled off from the copper foil to obtain a composite structure aramid fiber reinforced electrolyte membrane, and the composite structure aramid fiber reinforced electrolyte membrane is laminated and pressed to obtain an aramid fiber reinforced composite electrolyte membrane.
2. The large-scale manufacturing method of a high-toughness ceramic composite electrolyte membrane according to claim 1 is characterized in that: The polymer electrolyte raw material is a mixture of polyethylene oxide, polytetrafluoroethylene and lithium bis(trifluoromethylsulfonyl)imide; the mass ratio of polyethylene oxide and polytetrafluoroethylene in the solid electrolyte powder is (5-20): 100: (10-30); the addition ratio of lithium bis(trifluoromethylsulfonyl)imide to polyethylene oxide satisfies EO:Li= (8-20): 1; the addition amount of styrene-butadiene rubber latex is 1wt%~2.5wt% of the total mass of the mixture of solid electrolyte powder, polymer electrolyte raw material and styrene-butadiene rubber latex; the organic solvent is acetonitrile solvent; the solid content of the ceramic polymer electrolyte slurry is 40wt%~60wt%; the coating thickness of the coating machine is 80μm~120μm; the drying temperatures of the three-section oven are 90℃, 110℃ and 90℃ respectively.
3. The large-scale manufacturing method of a high-toughness ceramic composite electrolyte membrane according to claim 1, characterized in that: The method for preparing the nanoscale solid electrolyte powder comprises the following steps: The solid electrolyte raw material is ball-milled, dried and calcined at high temperature in sequence to obtain a solid electrolyte coarse powder; The solid electrolyte coarse powder is ball-milled, dried and sieved in sequence to obtain high-purity, nano-scale solid electrolyte powder.
4. The large-scale manufacturing method of a high-toughness ceramic composite electrolyte membrane according to claim 3 is characterized in that: In the step of sequentially ball-milling, drying and high-temperature calcining the solid electrolyte raw material to obtain a solid electrolyte coarse powder, the solid electrolyte raw material is one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide and lithium lanthanum zirconium tantalum oxide; the ball milling medium used in the ball milling process is isopropanol or ethanol, the ball-to-material ratio is (3-5): 1, the rotation speed is 200 rpm-500 rpm, and the ball milling time is 4h-6h; the drying temperature is 80°C, and the duration is 8h-12h; the roasting temperature in the high-temperature short calcination process is 850°C-1250°C, the duration is 4-8h, the heating rate is 2-8°C / min, and the cooling rate is 5-15°C / min.
5. The large-scale manufacturing method of a high-toughness ceramic composite electrolyte membrane according to claim 3 is characterized in that: In the step of ball-milling, drying and sieving the solid electrolyte coarse powder in sequence to obtain a high-purity, nano-scale solid electrolyte powder, the nylon screen of the vibrating screen used in the sieving process has a mesh number of 200-500 meshes.
6. The large-scale manufacturing method of a high-toughness ceramic composite electrolyte membrane according to claim 1, characterized in that: The pressure of the roller hot press is 2MPa~15Mpa, and the heating temperature is 45℃~80℃; the slitting length of the slitting machine is 50mm~170mm.
7. The large-scale manufacturing method of a high-toughness ceramic composite electrolyte membrane according to claim 1, characterized in that: The addition mass ratio of LiTFSI, PEO and EC / DMC is (0.5~1):(1~3):(0.2~0.5); the mass ratio of EC / DMC is (1:1); the mixing mass ratio of the ion gel and the pre-prepared aramid fiber suspension is (1~2):(0.4~0.7); the solid content of the ion gel is 20 wt%~35 wt%; the solid content of the aramid fiber suspension is 50 wt%~70 wt%.
8. The large-scale manufacturing method of a high-toughness ceramic composite electrolyte membrane according to claim 1, characterized in that: The preparation method of the aramid fiber suspension is as follows: dispersing the aramid fiber in a dimethyl sulfoxide liquid containing potassium hydroxide at room temperature for 1 to 3 days; the aramid fiber is a para-aramid or meta-aramid long fiber.
9. The large-scale manufacturing method of a high-toughness ceramic composite electrolyte membrane according to claim 1, characterized in that: The aramid gel is scraped onto the ceramic polymer electrolyte film, and after drying, it is peeled off from the copper foil to obtain a composite structure aramid fiber reinforced electrolyte membrane, and multiple layers of the composite structure aramid fiber reinforced electrolyte membrane are stacked and pressed to obtain an aramid fiber reinforced composite electrolyte membrane, wherein the scraping thickness is 20μm~50μm; the drying temperature is 80℃; the number of stacked layers is 2~5 layers; the pressing process uses a small heated roller press, the pressure is 2μm~10μm, the heating temperature is 60℃~80℃, and the roller gap is 40μm~100μm.
10. A high-toughness ceramic composite electrolyte membrane, characterized in that: The high-toughness ceramic composite electrolyte membrane is prepared by the large-scale manufacturing method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Multilayer composite solid electrolyte and preparation method thereof
CN112436180A
Semi-solid electrolyte membrane, preparation method thereof and semi-solid lithium ion battery
CN116435593A
Preparation method of high-ionic-conductivity condensed-state ceramic nanofiber-based solid electrolyte membrane, ceramic nanofiber-based solid electrolyte membrane and application method of ceramic nanofiber-based solid electrolyte membrane
CN118854688A
Multi-Layer Solid Electrolyte Separator for a Lithium Secondary Battery and Manufacturing Method
US20220407183A1